BIOM-52. A PROGNOSTIC GENE EXPRESSION RISK SCORE FOR MENINGIOMA. (9th November 2020) - Chen, William; Vasudevan, Harish N; Choudhury, Abrar; Lucas, Calixto-Hope G; Magill, Stephen; Susko, Matthew S; Braunstein, Steve; Boreta, Lauren; Nakamura, Jean; Sneed, Penny K; Bush, Nancy Ann Oberheim; Villanueva-Meyer, Javier; et al.
Abstract: BACKGROUND: Clinical biomarkers for identifying patients at risk for recurrence after resection of meningioma are lacking and are needed for guiding adjuvant therapy. The aim of this study was to identify a prognostic gene expression signature for meningioma. METHODS: Targeted gene expression analysis was performed on a discovery dataset of 96 meningiomas with suitable tissue identified from a retrospective institutional biorepository. Recurrence was dichotomized based on the median time to local recurrence (TTR). With median follow-up of 6.4 years, the discovery dataset was enriched for clinical endpoints of local recurrence (58%), mortality (42%), and disease-specific mortality (49% of deaths). A 266 gene expression panel was used to interrogate the discovery dataset, and a prognostic gene signature and risk score was generated using prediction analysis for microarrays (PAM) and elastic net regression. The risk score was validated using gene expression data (GSE58037) from 56 meningiomas resected at an independent institution (20% local recurrence, 18% mortality, median follow-up 5.4 years). RESULTS: A 36-gene signature was identified achieving an AUC of 0.86 for TTR faster than the median in the discovery cohort. A risk score between 0 and 1 based on this signature was strongly associated with shorter TTR (F-test, P< 0.0001), and on multivariate Cox regression (MVA), was independently associated with recurrence (RR 1.56 per 0.1 increase, 95% CI 1.30–1.90, P< 0.0001) and mortality (RR 1.32 per 0.1 increase, 1.07–1.64, P=0.01) after adjusting for WHO grade, age, extent of resection, and sex. Similarly, in the validation dataset, the gene risk score was correlated with shorter TTR (P=0.002) and associated with mortality on MVA (RR 1.86 per 0.1 increase, 1.19–2.88, P=0.005) after adjustment for WHO grade. CONCLUSIONS: The prognostic meningioma gene expression risk score presented here could be useful in identifying patients at higher risk of progression after resection.